Methodological Problems in Foreign Language Teaching: Is ict a Solution? - Zayas Martínez, Francisco (Rastros Rostros, 2014)
Foreign language teaching continues to be one of the issues to tackle in education. In recent decades,methodological approaches have prioritized communication over information around the way languagesfunction, but this has not led to a marked improvement in results. The newest models only offer partial or seeming improvements to some elements of teaching and learning processes. Editors’ systematicmisunderstanding of the process as a whole has turned methodological proposals into teaching fads thatare superficial, unproductive, and quick to fade away. In recent years we have looked to ict to provide away forward. This article argues that the quantity and immediacy of digital resources and telematics donot in themselves improve the efficacy of language teaching; they will only make a valuable contributionif built on careful educational planning that takes into account the time and dedication of individuals,their types and styles of learning, and the true cognitive nature of a language, not just the communicativebehavior that can be derived from it
Keywords: cognition; didactics; acquisitive teaching; foreign language; methodology; ict